2022
DOI: 10.1177/00220345221112332
|View full text |Cite
|
Sign up to set email alerts
|

Human Bone Marrow Cell Extracts Mitigate Radiation Injury to Salivary Gland

Abstract: Mitigation of irradiation injury to salivary glands was previously reported using a cell-free extract from mouse bone marrow. However, to bring this potential therapy a step closer to clinical application, a human bone marrow cell extract (BMCE) needs to be tested. Here, we report that irradiation-induced injury of salivary glands in immunocompetent mice treated with human BMCE secreted 50% more saliva than saline-injected mice, and BMCE did not cause additional acute inflammatory reaction. In addition, to ide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 29 publications
0
2
0
1
Order By: Relevance
“…This approach exhibited a therapeutic effect comparable to MSCs in NOD mice (Abughanam et al, 2019). Another study showed that this strategy can be used to treat irradiation‐injured SGs, as cell extracts of adipose‐ and BM‐derived MSCs or salivary gland stem cell containing numerous angiogenesis‐related growth factors restored the function of radiogenic SGs (Fang et al, 2018; Su et al, 2020; Su, Liu, et al, 2022; Su, Pillai, et al, 2022). Additionally, our preliminary data demonstrated that cell extracts do not accelerate tumor growth.…”
Section: Experimental Approaches Using Cell‐based Therapies For Sg Hy...mentioning
confidence: 99%
“…This approach exhibited a therapeutic effect comparable to MSCs in NOD mice (Abughanam et al, 2019). Another study showed that this strategy can be used to treat irradiation‐injured SGs, as cell extracts of adipose‐ and BM‐derived MSCs or salivary gland stem cell containing numerous angiogenesis‐related growth factors restored the function of radiogenic SGs (Fang et al, 2018; Su et al, 2020; Su, Liu, et al, 2022; Su, Pillai, et al, 2022). Additionally, our preliminary data demonstrated that cell extracts do not accelerate tumor growth.…”
Section: Experimental Approaches Using Cell‐based Therapies For Sg Hy...mentioning
confidence: 99%
“…Так, для отримання кріоекстракту клітин культивовані чи нативні клітини ресуспендують у 0,9 % фізіологічному розчині до концентрації 10 7 клітин/100 мкл та проводять 3 цикли заморожування (-80°C) та відтавання (37°C) для лізису клітин. Після центрифугування при 17000 g протягом 30 хв при 4°C супернатант (визначений як клітиннй екстракт) зберігають при -80°C до використання [9,10,11].…”
Section: огляд літературиunclassified
“…To date, various experimental approaches of cell-based therapy employing gland epithelial stem/progenitor cells and/or mesenchymal stem cells (MSCs) have been examined for restoring the function of IR-damaged SGs [10][11][12][13][14][15][16]. Among these approaches, MSC therapy for atrophic SGs using intraglandular or intravenous injection of cells has been shown to slow the atrophic process by paracrine effects via induction of polarization of activated macrophages towards an anti-inflammatory phenotype (M2-type) at injury sites [13][14][15][16][17][18]. These macrophages contribute to revascularization and the following tissue regeneration [19][20][21].…”
Section: Introductionmentioning
confidence: 99%